Pengembangan Media Penilaian Otentik IPA Berbasis Keterampilan Abad 21 untuk Siswa Sekolah Dasar - Aris Naeni Dwiyanti; Galuh Rahayuni (Jurnal Inovasi Pendidikan Dasar, 2020)
The development of technology makes students have many soft skills in facing the demands of the 21st century. These soft skills are better known as century skills, where students expect to develop the potential of these soft skills as preparation for the future. Progress of these soft skills can train using authentic science assessment media. Media contains material sketches, skill literacy, competency tests, and follow-up programs. Each content can develop children's soft skills in cooperation, communication, creativity, and students' critical thinking. This research includes research and development research. The initial stage of this research was to analyze the content needs of the authentic science assessment media, and a limited trial carried out if deficiencies improvements were made. This study's subjects were students, elementary school teachers, linguists, media experts, material experts, and assessment experts. Purpose the research aims to develop media authentic science assessment-based Century skills for elementary school students and know the quality of authentic science assessment media. The mean validation results from media experts, material experts, linguists, and assessment experts were 84.5%, 84.5%, 84.5%, and 82.5%. Based on these results, authentic science assessment media are good in content, language, and presentation.   Keywords: Science, authentic assessment media, century skills, elementary school